Small world : a novel - Evison, Jonathan (Dutton, an imprint of Penguin Random House, 2022)
"From the New York Times bestselling author of West of Here, a novel that chronicles a hundred-and-seventy years of American nation-building from numerous points-of-view across place and time, and explores the Great American Experiment from its formative days to the present moment and asks whether or not our nation has made good on its promises"--